Pengaruh Kompensasi Finansial dan Kompensasi Non Finansial Terhadap Turnover Intention Karyawan Pada Commanditaire Vennootschap Berlian chemical - Putri Mautia Lestari; Muhammad Ichwan Musa; Rezky Amalia Hamka; Romansyah Sahabuddin (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to determine the influence of financial and non-financial compensation on employee turnover intention—both individually and simultaneously—at CV. Berlian Chemical Mandiri. The primary focus is to analyze the extent to which the company's compensation system mitigates employees' desire to leave their jobs, particularly given the high turnover rates experienced by the firm. A quantitative approach utilizing a survey method was employed. Data were collected via questionnaires distributed to all 38 employees of CV. Berlian Chemical Mandiri using a saturated sampling technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to examine the relationships between the variables: financial compensation, non-financial compensation, and turnover intention. The results indicate that both financial and non-financial compensation have a significant negative effect on employee turnover intention, whether considered individually or simultaneously. This suggests that superior compensation—whether financial or non-financial corresponds to a lower desire among employees to leave the company. The findings also highlight the crucial role of non-financial compensation in fostering workplace satisfaction and employee engagement, thereby enhancing retention and reducing the company's high turnover rate.